Hybridity and National Identity different perspectives of two national folk dance companies in the Philippines. - Namiki, Kanami (2011)
This paper will examine how Philippine folk dance performances by two state-sponsored folk dance groups, the Bayanihan Philippine National Folk Dance Company (Bayanihan) and the Ramon Obusan Folkloric Group (ROFG), both resident companies of the Cultural Center of the Philippines (CCP), has produced and developed the concept of hybridity, a dominant narrative of national identity and art style/form in postcolonial Philippines. The two dance companies have developed different dance styles/forms and staging approaches, representing two contrasting traditions of hybridity, which have brought about different effects to form and inform national identity. By comparing the two groups, I will analyze how they show different perspectives on the concept of hybridity, and hopefully present the specific way in which the two groups and their hybridity form and inform a national identity through Philippine folk dance performance.
Keywords: Philippine folk dancing; Dance companies